Occurrence and fate of pesticides in the Argentine stretch of the Paraguay-Paraná basin - Etchegoyen, María Agustina (2017)
The Argentine stretch of the del Plata basin crosses regions devoted to extensive and intensive agriculture mostly with chemical pest control. The utilization of pesticides in the region has increased 900% in the last two decades associated with the introduction of biotech crops and direct-seeding techniques. Our objective was to study the occurrence, concentration, and fate of pesticides in surface water and bottom sediments of the principal tributaries and main watercourse of the Paraguay-Paraná River. We sampled 22 sites in the distal positions of the main affluents and main watercourse of the Paraná and report here results from two monitoring campaigns (2010–2012). Surface water and bottom sediments were analyzed according to standardized methods by matrix-solid-phase dispersion and liquid-liquid extraction, respectively. Twenty-three pesticide compounds were analyzed by gas chromatography. The results from both campaigns indicated a generalized but variable distribution in the concentrations detected throughout the basin. The ranges of total measured pesticide concentrations in water and sediments were, respectively, 0.004–6.62 μg/l and 0.16–221.3 μg/ kg dry weight. Endosulfans, cypermethrin, and chlorpyrifos were ubiquitous compounds in both environmental compartments and quantitatively the most relevant. All concentrations detected in water were over the recommended guidelines for the protection of aquatic biota. The partitioning indicated a higher affinity for the sediments. Agricultural activity is the source of pesticide-pollution loads, transported by tributaries that reach the main watercourse and alter the quality of the aquatic ecosystem.